EVALUATION OF THE WASTE MANAGEMENT IN GORONTALO CITY - Fuad, Mohamad Januar (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
Environmental problem commonly found in the urban area is the poor waste management. This research aimed to investigate the conditions of the waste management on Gorontalo City and the solution of its problems, so that it could be made as inputs for the Government in selecting the services for the waste management was more efficient and effective. The research method used approach which was normative descriptive and comparative descriptive. The descriptive approach was a research with the pattern of illustrating what existing in the field and tried to illustrate the data. The descriptive normative approach was condusted to evaluate the method of the waste management in Gorontalo City through the evaluation of the standard (normative) and existing theory. In order to achieve this target, the primary data which were obtained from the survey and interviews conducted in the fields were needed. The research results indicated that the amount produced in Gorontalo City was to 539.92 tons/day. Therefore, the need for the facilities and infrastructures for the waste/structured were 4 ritase of Dump Trucks, 4 ritase Arm Roll Trucks, 487 units of trash bins, 23 units of TPS containers, 3 units of TPST, 54 units of garbage collective carts, 4 units of Dump Trucks, 6 units of Arm Roll Trucks, and ​​29.71 Ha of TPS area. As for the aspect of waste management activities/unstructured, the public, the public participation in dealing with the generated wastes and the potentially recycled wastes, and the regulations were still categorized as having the bad value. The distance between the waste sourcces and the TPS was still evaluated as not good. The calculation revealed the evaluation result of the waste management in Gorontalo City had not met the expected standard (not good) consequently, the result of the waste management had not been maximum.